Propriedades farmacológicas dos monoterpenos α- e β-pineno no músculo liso gastrintestinal de ratos : efeito miorrelaxante e pró-cinético - Jucá, Davi Matthews (2007)
The monoterpenes α- and β-pinene are constituents commonly found in several essential oils obtained from plants in Brazilian northeast such as “malva-santa” and “eucalipto”, which are used in folk medicine to treat respiratory and gastrointestinal dysfunctions. Myorelaxant actions are due to the presence of these constituents in their essential oils. The present work aimed to further study the pharmacological effects of these compounds on smooth muscle gastrointestinal contractility as well as on liquid gastric emptying in rats. Wistar rats (200-250 g) were used, sacrificed by cervical dislocation. Strips were carefully obtained from gastric fundus, duodenum and ileum, and were maintained in Tyrode’s solution. Isometric contractions were recorded through force transducers coupled to a computerized data acquisition system. Solutions containing α- or β-pinene were prepared with Tween 80 (final concentration ≤ 0,2% v/v). Solely used, α- or β-pinene decreased duodenal basal tonus with IC50 value corresponding to 655.1 µM and 810.2 µM, respectively. Submaximal contractions induced by K+ (60 mM, K60) or acetylcholine (ACh, 3 µM) were inhibited, in a concentration-dependent manner (p < 0.001, ANOVA), with IC50 values of 790.0 [580.2-1007.4] e 760.0 [650.6-870.8] µM, respectively to α-pinene and 770.1 [500.3-1180.5] e 620.7 [520.9-750.2] µM, respectively to β-pinene. In tissues pre-treated with α- (1 mM) or β-pinene (1 mM) in medium without Ca2+ with EGTA (0.2 mM), ACh (3 µM)-induced phasic contractions were inhibited from 18.4 ± 3.3% to 7.7 ± 1.5% and 5.0 ± 1.2% of K60, respectively. In tissues maintained under Ca2+-free conditions (in medium containing EGTA 0.2 mM) and in presence of K+ (60 mM) or ACh (3 µM), tonic contractions induced by Ca2+ addition were reduced from 50.2 ± 3.3% and 53.9 ± 5.2%, respectively to values corresponding to 10.6 ± 2.6 % and 24.4 ± 4.1 % to experiments with α-pinene and 6.6 ± 1.1 % and 10.9 ± 3.5 % to experiments with β-pinene, respectively. In tissues pre-treated with α- (1 mM) or β-pinene (1 mM), ACh (60 µM)-induced tonic contractions, in verapamil (3 µM)-containing medium, were inhibited from 29.0 ± 4.1 % to 10.6 ± 2.7 % and 12.5 ± 2.2 % of the K60, respectively. The caffeine (20 mM)-induced contractile response in normal Tyrode’s solution was potentiated from 47.8 ± 3.2 % to 72.1 ± 9.0 and 88.8 ± 10.6 % of the control response in virtue of α- (1 mM) or β-pinene (1 mM) presence, respectively. In EGTA-containing Ca2+-free medium, the contractile response to caffeine was reduced to 9.5 ± 3.5%. Under these conditions, and in presence of α- (1 mM) or β-pinene (1 mM), this response was not significantly altered, with values corresponding to 7.2 ± 2.2 e 4.7 ± 1.3 %, respectively. In verapamil- and EGTA-containing Ca2+-free medium, after depletion of the intracellular Ca2+ stores by CCh (100 µM), the contractions induced by Ca2+ addition were potentiated by the presence of α- (1 mM) or β-pinene (1 mM) from 30.7 ± 2.1 % to 80.6 ± 4.7 and 51.3 ± 7.6 %, respectively (p < 0.05, Bonferroni’s test). In gastrointestinal dye fractional retention studies, α- or β-pinene increased the rat liquid gastric emptying. On the other hand, they did not alter the ACh-induced contractions on gastric fundus strips. Our study firstly shows that, both α- and β-pinene have prokinetic properties in rats. In isolated tissues, they did not affect cholinergic contractions on gastric fundus strips, but are myorelaxant compounds on rat duodenal preparations, probably by an interference with cellular mechanisms mediated by IP3 release. Moreover, α- and β-pinene activate capacitative Ca2+ entry to intracellular milieu after Ca2+ stores depletion.